2011
DOI: 10.1007/s15010-010-0070-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of earlier HAART initiation on the immune status and clinical course of treated patients on the basis of cohort data of the German Competence Network for HIV/AIDS

Abstract: The results gave a strong hint for a therapy initiation at higher CD4-cell-count/μl regarding the outcome of death in treated patients. A distinct benefit was shown regarding the first decline of CD4-cell-count/μl below 200.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Despite nearly 15 years of experience with antiretroviral therapy for the treatment of HIV-positive individuals, consensus on the optimal time to initiate HAART has yet to be reached [82]. Aggressive early treatment in the course of infection was initially purported to present significant side effect risks and development of drug resistance [83].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite nearly 15 years of experience with antiretroviral therapy for the treatment of HIV-positive individuals, consensus on the optimal time to initiate HAART has yet to be reached [82]. Aggressive early treatment in the course of infection was initially purported to present significant side effect risks and development of drug resistance [83].…”
Section: Discussionmentioning
confidence: 99%
“…Aggressive early treatment in the course of infection was initially purported to present significant side effect risks and development of drug resistance [83]. Plettenburg et al [82] recently identified that initiation of HAART in patients with higher CD4 counts correlated with improved outcomes. Aggressive and early treatment, even in asymptomatic HIV-positive patients, is recommended by most clinicians [84].…”
Section: Discussionmentioning
confidence: 99%
“…Only one trial has randomized people with a CD4 cell count >350 cells/μL, but this used a comparator arm of delay of initiation of ARVs until the CD4 cell count has fallen below 250 cells/μL, and thus is likely to overestimate the apparent benefits of immediate treatment compared with starting at <350 cells/μL. There have been a number of observational studies that have attempted to address this issue , which have produced conflicting findings. Some of these studies have failed to take into account the lead time between an individual's CD4 cell count falling below the threshold for treatment and the date of starting treatment ; as this may introduce serious bias into treatment comparisons, these results do not resolve the question whether it is better to start ART at higher CD4 cell counts.…”
Section: Chronic Infectionmentioning
confidence: 99%
“…There have been a number of observational studies that have attempted to address this issue , which have produced conflicting findings. Some of these studies have failed to take into account the lead time between an individual's CD4 cell count falling below the threshold for treatment and the date of starting treatment ; as this may introduce serious bias into treatment comparisons, these results do not resolve the question whether it is better to start ART at higher CD4 cell counts.…”
Section: Chronic Infectionmentioning
confidence: 99%
“…There may be additional challenges for ART uptake and adherence for HIV-positive MSM with high CD4 levels, as both Chinese and international data suggest that higher CD4 level is associated with lower ART coverage [11,12]. Since PLWH with CD4 levels> 350 cells/mm 3 have only recently become eligible to receive free ART after the updating of national guidelines, the ART coverage of this group may be an indicator of whether guidelines are being successfully implemented. Prior to the updating of national ART guidelines, a cross-sectional study reported that only 18% of HIV-positive MSM with CD4 levels> 350 cells/mm 3 were on ART [13].…”
Section: Introductionmentioning
confidence: 99%